An integrative taxonomy investigation unravels a cryptic species of Mobula Rafinesque, 1810 (Mobulidae, Myliobatiformes), from the Atlantic Ocean - Nayara Bucair; Silvia Hinojosa-Alvarez; Andrea Denise Marshall; Jessica Pate; Carlo Leopoldo Bezerra Francini; Amana Guedes Garrido; Katia Cristina Cruz Capel; Thiago Silva Loboda; Jhonatas Sirino Monteiro; Carlos Eduardo Malavasi Bruno; Claudia Francesca Vaga; Alistair D. M. Dove; et al. (Environmental Biology of Fishes, 2025)

Paleoecological history of Eleuthera Island, the Bahamas, based on pollen and charcoal analyses from two lakes - Eric Kjellmark; Lisa Park Boush; Amy Myrbo; Mary Jane Berman; Perry Gnivecki (Journal of Paleolimnology, 2024)

Neighborhood violence and socioeconomic deprivation influence associations between acute air pollution and temperature on childhood asthma in New York city - Rachit Sharma; Jamie L. Humphrey; Lisa Frueh; Ellen J. Kinnee; Perry E. Sheffield; Jane E. Clougherty (Environmental Research, 2023)

Examining the performance of alternative harvest regulations for short-lived taxa: A case study of Florida Bay scallop management - Lisa Chong; Nicholas Fisch; John Scott Borsum; Jennifer Granneman; Diana Perry; Gabrielle Love; Brittany Hall-Scharf; Robert Botta; Kai Lorenzen; Edward Camp; Zachary Siders (Fisheries Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Hydrogeology of Wadi Wurayah, United Arab Emirates, and its importance for biodiversity and local communities - Christophe Tourenq; Mike Brook; Sandra Knuteson; Maral Khaled Shuriqi; Moaz Sawaf; Lisa Perry (Hydrological Sciences Journal, 2011)

Involvement of ERK1/2 and p38 in Mg2+ accumulation in liver cells - Lisa M. Torres; Christie Cefaratti; Beverly Perry; Andrea Romani (Molecular and Cellular Biochemistry, 2006)

Preliminary evidence of attenuation of the disruptive effects of the NMDA glutamate receptor antagonist, ketamine, on working memory by pretreatment with the group II metabotropic glutamate receptor agonist, LY354740, in healthy human subjects - John H. Krystal; Walid Abi-Saab; Edward Perry; D. Cyril D’Souza; Nianjin Liu; Ralitza Gueorguieva; Lisa McDougall; Tracy Hunsberger; Aysenil Belger; Louise Levine; Alan Breier (Psychopharmacology, 2005)

Interspecific Interactions Between Cebus capucinus and Other Species: Data from Three Costa Rican Sites - Lisa M. Rose; Susan Perry; Melissa A. Panger; Katharine Jack; Joseph H. Manson; Julie Gros-Louis; Katherine C. Mackinnon; Erin Vogel (International Journal of Primatology, 2003)

Resolving phytoplankton photoprotective : photosynthetic carotenoid ratios on fine scales using in situ spectral absorption measurements - Lisa B. Eisner; Michael S. Twardowski; Timothy J. Cowles; Mary Jane. Perry (Limnology and Oceanography, 2003)
Temporal changes in phytoplankton pigments and spectral absorption were evaluated during June 1998 in East Sound, Orcas Island, Washington. High‐resolution vertical profiles of in situ spectral absorption were obtained with a Wet Labs ac‐9 (nine‐wavelength absorption and beam attenuation meter), and pigment concentrations were determined for discrete water samples using high‐performance liquid chromatography (HPLC). Fucoxanthin was the most abundant carotenoid, indicating the dominance of diatoms. We computed a slope index to evaluate changes in shapes of the in situ particulate absorption coefficient ( a p ) spectra, a p slope = ( a p 488 − a p 532)/( a p 676(488 − 532 nm)). A clear linear relationship was seen between ratios of photoprotective : photosynthetic carotenoids (PPC : PSC) and these a p slopes. While pigment package effects may alter the absorption spectra, in our data set we still found a significant relationship between pigment ratios and in situ a p slopes. Retrieval of this relationship was facilitated by the low and relatively constant detrital absorption coefficient ( a d ) values in our study area. Similar relationships were found between PPC:PSC ratios and the estimated phytoplankton absorption coefficient ( a ph ) spectra. High PPC:PSC ratios and steeper a p slopes were associated with high‐light levels. Our results suggest that in situ absorption measurements can be used to estimate PPC:PSC ratios in areas where the ad contribution is low or can be estimated. These variations in pigment ratios and spectral absorption reflect photoacclimation responses and/or changes in phytoplankton species composition and suggest in situ absorption measurements may be used to estimate pigmentation changes over fine temporal and spatial scales.

Temporary alteration of local social structure in a threatened population of Cuban iguanas ( Cyclura nubila ) - Allison Alberts; Jeffrey Lemm; Andrew Perry; Lisa Morici; John Phillips (Behavioral Ecology and Sociobiology, 2002)

Dynamics of Female–Female Relationships in Wild Cebus capucinus: Data from Two Costa Rican Sites - Joseph H. Manson; Lisa M. Rose; Susan Perry; Julie Gros-Louis (International Journal of Primatology, 1999)

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)